Pengaruh Model Pembelajaran Team Quiz Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas XI IPA SMA Negeri Kaureh Kabupaten Jayapura - Satrama Royal Hadinata (Departement of Mathematics Education, 2022)
The ability of students to understand mathematical concepts is the initial capital for students to solve all forms of problems in mathematics. Given the importance of understanding mathematical concepts for students in solving mathematical problems and the team quiz learning has never been applied by the teacher in learning mathematics, a study was conducted to see the effect of the team quiz learning model on students' ability to understand mathematical concepts. This research approach is a quantitative quasi-experimental type with a non-equivalent control group design. The sampling technique is random sampling. The data collection technique of this research is a test. The instrument used is a written test in the form of an essay. The data analysis technique is prerequisite test (normality test using the Lilliefors analysis method and homogeneity test using the one way anova analysis method and hypothesis testing using the normalized gain analysis method (n-gain) and independent sample t test. The results show that there is an effect of the team quiz learning model on the ability to understand mathematical concepts.